Prove cos(a+b)cos(a-b)=cos^2b-sin^2a ?

1 Answer
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

43
Apr 22, 2017

Answer:

See proof below

Explanation:

We need

#(x+y)(x-y)=x^2-y^2#

#cos(a+b)=cosacosb-sina sinb#

#cos(a-b)=cosacosb+sina sinb#

#cos^2a+sin^2a=1#

#cos^2b+sin^2b=1#

Therefore,

#LHS=cos(a+b)cos(a-b)#

#=(cosacosb-sina sinb)(cosacosb+sina sinb)#

#=cos^2acos^2b-sin^2a sin^2b#

#=cos^2b(1-sin^2a)-sin^2a(1-cos^2b)#

#=cos^2b-cancel(cos^2bsin^2a)-sin^2a+cancel(cos^2bsin^2a)#

#=cos^2b-sin^2a#

#=RHS#

#QED#

Was this helpful? Let the contributor know!
1500
Impact of this question
6499 views around the world
You can reuse this answer
Creative Commons License